FTIR spectroscoptc study and antifungal activity of the medicinal plant glory lily (Gloriosa superba) - P. Kabilar, P. Paneerselvam1, M. Gayathri2, S. Ravi1*, S. Ashokkumar, K. Mallika1 (Journal of Experimental Sciences, 2011)
In this present study, the presence of the phyto compound (i.e.) Colchicine and other chemical constituents present in three different treated tuber and seed samples of Glory Lily (Gloriosa superbd) was confirmed using FTIR. An attempt has been made to correlate the extinction coefficient (K) values of all the samples. And also the samples were extensively studied for their antifungal activity against Pseudomonas aeruginosa, Klebsiella phemoniae, and Salmonella typhi. The results indicated that the Organic Manure treated samples were highly active against the three fungi.